ITRAQ‐based quantitative proteomic analysis in liver of Pomacea canaliculata induced by oleanolic acid stress. Issue 8 (3rd June 2022) - Yu, Jiaqi; Cen, Xiaofeng; Chen, Guifeng; Tang, Mingli; Mo, Ling; Li, Jingjing
Abstract: Background: Triterpene acid is one of the typical active constituents of Eucalyptus bark, which is the main by‐product of the Eucalyptus wood industry. Our studies have demonstrated that triterpene acid stress could inhibit climbing and increase mortality in Pomacea canaliculata (Lamarck). However, limited attention has been paid to the proteomic responses of this snail under triterpene acid stress. Result: Using iTRAQ‐based quantitative proteomics, we elucidated the regulatory mechanism in the livers of P. canaliculata held in chlorine‐free water and exposed to 100 mg L −1 oleanolic acid (OA) for 24 h. A total of 4308 proteins were identified, of which 274 were differentially expressed proteins (DEPs) including 168 (61.31%) differentially upregulated proteins and 106 (38.69%) differentially downregulated proteins. Bioinformatics analysis revealed that P. canaliculata responses to OA stress are mainly involved in glucose metabolism, energy synthesis, immune response, stress response, protein synthesis, and apoptosis. According to KEGG analysis, the 274 DEPs were mapped to 168 KEGG pathways and 10 KEGG pathways were significantly enriched ( P < 0.05). Furthermore, qRT‐PCR was performed for histone H4, catalase, isocitrate dehydrogenase, superoxide dismutase, ferritin, lipase, and tropomyosin to validate the iTRAQ results. Conclusion: Proteomic analysis suggested that OA stress led to the disruption of glucose metabolism, energy synthesis, and protein synthesis, and triggered a series of molecular pathways containing many key proteins involved in the immune process, thereby helping P. canaliculata resist OA stress. © 2022 Society of Chemical Industry. Abstract :